Language Testing System In Teaching-Learning Process - Shridhar Sumanchandra Brahmbhatt (Elementary Education Online, 2023)
Many language teachers distrust the test and testers, and this is not wrong because out language testing system is very poor, which could harm teaching and learning and often fail to accurately measure whatever is intended. So, the present question will focus on improving the way of testing.